Cardiac and Muscular Involvement in Idiopathic Inflammatory Myopathies: Noninvasive Diagnostic Assessment and the Role of Cardiovascular and Skeletal Magnetic Resonance Imaging - Mavrogeni, Sophie; P. Sfikakis, Petros; Dimitroulas, Theodoros; Kolovou, Genovefa; D. Kitas, George (Inflammation & Allergy-Drug Targets (Discontinued), 2014)
Idiopathic inflammatory myopathies (IIMs) are rare autoimmune diseases and include dermatomyositis, polymyositis, necrotizing myopathy and inclusion body myositis; they are characterized by inflammation of skeletal muscle and other internal organs and may potentially lead to irreversible damage and death. Only a small percentage of IIM has clinically overt cardiac disease; however, heart involvement is one of the leading causes of death and therefore, early detection remains a challenge. Biochemical markers and non-invasive methods such as the electrocardiogram and echocardiography have a role in diagnosis, but lack sensitivity in identifying patients with early, sublinical cardiac abnormalities. Endomyocardial and skeletal muscle biopsies are very useful, but invasive techniques and cannot be used for routine follow-up. Cardiac and skeletal magnetic resonance imaging, due to their capability to perform tissue characterization, has emerged as novel techniques for the early detection and follow-up of myocardial and skeletal muscle tissue changes (oedema, inflammation, fibrosis) in IIM. However, the clinical implications of using these approaches and their cost /benefit ratio require further evaluation.
Keywords: myocarditis